2016
DOI: 10.1063/1.4962423
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the micro-structure and depletion potentials in two-dimensional binary mixtures of additive hard-disks

Abstract: Depletion forces are a particular class of effective interactions that have been mainly investigated in binary mixtures of hard-spheres in bulk. Although there are a few contributions that point toward the effects of confinement on the depletion potential, little is known about such entropic potentials in two-dimensional colloidal systems. From theoretical point of view, the problem resides in the fact that there is no general formulation of depletion forces in arbitrary dimensions and, typically, any approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…We also use the simulation and theoretical results to provide new insights concerning the physics of ultra-dense highly correlated fluids. Concerning the new theoretical aspect, we consider the Modified-Verlet (MV) closure [20][21][22][23]. It was shown long ago [20,21] to produce very accurate results for pair structure and thermodynamic properties of monodisperse hard spheres in the "normal" liquid regime below the crystallization packing fraction of ~0.495 where glassy dynamics has not yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…We also use the simulation and theoretical results to provide new insights concerning the physics of ultra-dense highly correlated fluids. Concerning the new theoretical aspect, we consider the Modified-Verlet (MV) closure [20][21][22][23]. It was shown long ago [20,21] to produce very accurate results for pair structure and thermodynamic properties of monodisperse hard spheres in the "normal" liquid regime below the crystallization packing fraction of ~0.495 where glassy dynamics has not yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting and natural result obtained from Eq. ( 2), and confirmed by independent experiments and molecular simulations [12], is that the effective potential tends to the potential of mean force when only a few large particles are present (the leading term in b eff ll (r) is quadratic in n l [11]), even for high concentrations of small particles. The correlation terms in Eq.…”
mentioning
confidence: 63%
“…As stressed out above, one focus of colloidal science research is concerned with determining particle-particle effective interactions. More specifically, by means of the multicomponent Ornstein-Zernike equation, a theoretical approx-imation that accounts for the effective interactions between colloids when part of the system is integrated out of the description has been successfully developed [49,50]. As we will explain in detail in the following section, this approximation can be used, for example, to determine the phase behavior of a colloidal binary mixture and the depletion forces between large colloids [49].…”
Section: Theoretical Framework and Molecular Modelingmentioning
confidence: 99%
“…For example, within the integral equations theory of liquids for the effective interactions, one takes advantage of the covariant property of the Ornstein-Zernike equation when the degrees of freedom of the unobservable components of the fluid are integrated out from the description and are fully taken into account within the effective potential between the observable molecules [75,76], i.e., colloids. This theoretical approximation represents a good starting point since it has been demonstrated that it quantitatively describes the effective potential among macromolecules when compared with either molecular simulations or experiments [50] and can be accurately applied near to non-equilibrium conditions [49]. In particular, this formalism has been used to understand the depletion forces between colloids, see, e.g., Refs.…”
Section: Effective Interactions Between Colloids Near Nonequilibrium Thermodynamic Statesmentioning
confidence: 99%
See 1 more Smart Citation